A Challenges in Measuring the Effectiveness of Public Organizations: A Review of Selected Models - Gródek-Szostak, Zofia; Gurgul, Henryk; Dubiel, Nina (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
Against the backdrop of a turbulent environment and changing economic, social, and technological realities, public sector organizations are facing the challenge of improving the effectiveness of their operations. The concept of New Public Management (NPM), drawing from private sector solutions, has significantly contributed to the reorganization of public administration through workforce reduction, decentralization, and privatization, with a focus on performance management. Academic literature continues to seek answers regarding the internal and external conditions for measuring effectiveness in public institutions, including higher education institutions. A particularly important role in the public sector is played by Business Environment Institutions (BEIs) – non-profit entities that bridge the gap between market mechanisms and public administration activities, becoming partners in the achievement of public goals. This article aims to identify and critically assess models for measuring the effectiveness of public organizations that can be adapted to evaluate the performance of public Business Environment Institutions. The analysis is based on theoretical perspectives, such as structural contingency theory and new institutional organization theory, in order to explain both the diversity and the tendency towards isomorphism in the institutions under consideration